2017
DOI: 10.1038/s41598-017-04770-x
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Vulnerabilities of Cancer Cells to the Cold Atmospheric Plasma-Stimulated Solutions

Abstract: Cold atmospheric plasma (CAP), a novel promising anti-cancer modality, has shown its selective anti-cancer capacity on dozens of cancer cell lines in vitro and on subcutaneous xenograft tumors in mice. Over the past five years, the CAP-stimulated solutions (PSS) have also shown their selective anti-cancer effect over different cancers in vitro and in vivo. The solutions used to make PSS include several bio-adaptable solutions, mainly cell culture medium and simple buffered solutions. Both the CAP-stimulated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 64 publications
7
84
0
Order By: Relevance
“…Xiang L et al reported that PAM could selectively reduce the cell viability of triple negative breast cancer cells 23 . Cell death was also induced by treatment with PAM in other types of cancers, including pancreatic cancer, glioblastoma, squamous head and neck cancer, and melanoma [24][25][26] . These authors presumed that the underlying mechanism of cell death was related to increased apoptosis through the accumulation of intracellular reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…Xiang L et al reported that PAM could selectively reduce the cell viability of triple negative breast cancer cells 23 . Cell death was also induced by treatment with PAM in other types of cancers, including pancreatic cancer, glioblastoma, squamous head and neck cancer, and melanoma [24][25][26] . These authors presumed that the underlying mechanism of cell death was related to increased apoptosis through the accumulation of intracellular reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma generates reactive oxygen and nitrogen species (RONS), which, once applied to cancer cells, have the potential to induce DNA damages leading to cell apoptosis [1] or cause immunogenic cell death [2][3][4]. More importantly, cancer cells appear to be more sensitive to plasma than healthy cells [5][6][7][8][9]. This selectivity could be explained by the RONS-induced stress tolerance threshold, which is higher in normal cells than cancer cells, due to their increased production of reactive oxygen species [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…They found that these two amino acids in plasma‐treated PBS are highly effective in consuming the plasma‐generated hydrogen peroxide and confirmed this also for the cell culture medium DMEM . Furthermore, the treatment of cells with N ‐acetyl cysteine could prevent cell injury by CAP …”
Section: Resultsmentioning
confidence: 71%